The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fmicb.2021.664810
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Novel Salmonella Phage vB_SalP_TR2

Abstract: Salmonella is a widely distributed foodborne pathogen. The use of Salmonella phages as biocontrol agents has recently gained significant interest. Because the Salmonella genus has high diversity, efforts are necessary to identify lytic Salmonella phages focusing on different serovars. Here, five Salmonella phages were isolated from soil samples, and vB_SalP_TR2 was selected as a novel phage with high lytic potential against the host Salmonella serovar Albany, as well as other tested serovars, including Corvall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 68 publications
4
32
0
Order By: Relevance
“…Heating could cause irreversible damage to phage particles, such as irreversible unfolding and dissociation of structural proteins, damage to the portal complex, disintegration of phage into head and tail, and leakage of DNA ( Ahmadi et al, 2017 ). Shang et al (2021) visualized the heat-treated phages with a transmission electron microscope. The detrimental effects of heat on phage structure were evidenced by phage tail aggregation, detachment of phage head and tail, and empty capsid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Heating could cause irreversible damage to phage particles, such as irreversible unfolding and dissociation of structural proteins, damage to the portal complex, disintegration of phage into head and tail, and leakage of DNA ( Ahmadi et al, 2017 ). Shang et al (2021) visualized the heat-treated phages with a transmission electron microscope. The detrimental effects of heat on phage structure were evidenced by phage tail aggregation, detachment of phage head and tail, and empty capsid.…”
Section: Resultsmentioning
confidence: 99%
“…It is expected that higher MOI and longer incubation time may be needed to achieve the same log reduction in cell concentration if using solid food matrices. Shang et al (2021) evaluated the ability of phage vB_SalP_TR2 to reduce Salmonella Albany contamination in pasteurized milk and chicken meat stored at 37°C for 6 h. They found that the phage was much more effective against S . Albany in pasteurized milk than in chicken meat ( Shang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The filtrate (5 mL) was then mixed with 5 mL double-strength TSB pre-inoculated with 1% of overnight-cultured host strain and incubated at 37°C in a shaker at 160 rpm for 12 h. After the mixture had been centrifuged at 8000 rpm and filtered, phage presence was verified using the conventional double-layer agar method ( Van Twest and Kropinski, 2009 ; Guo et al, 2021 ). Double-layered agar plates were incubated at 37°C for 18 ± 2 h for visualization and single plaques on the plates were purified five times to obtain a pure phage isolate ( Duc et al, 2020 ; Shang et al, 2021 ). Phage propagation was performed as described previously ( Lu et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…During the incubation period, 100 μL of the mixture was collected at 10 or 20 min intervals to calculate phage titer using the double-layer agar assay. Phage survival at different temperatures and pH values was assessed as described previously ( Shang et al, 2021 ). Briefly, phage suspensions (approximately 10 9 PFU/mL) were incubated at 30, 40, 50, 60, 70, or 80°C for 1 h to test thermal stability and at pH levels from 2 to 12 for 12 h to test pH stability.…”
Section: Methodsmentioning
confidence: 99%